Pengaruh Implementasi Kurikulum 2013 dan Cara Belajar Siswa Terhadap Pembelajaran Matematika - Sofie Dinia; Eva Dwi Minarti (Jurnal Inovasi Matematika, 2019)
This study aims to look at the effect of the implementation of the 2013 Curriculum in mathematics learning according to students of class XI in one West Bandung District School. The research method used is a survey. Data obtained by giving questionnaires to students, then analyzed descriptively. Questionnaire consists of 16 items of statements regarding the implementation of 2013 Curriculum implementation and how students learn in mathematics learning. The research subjects consisted of 36 students. The results showed 36% of students agreed to the use of the 2013 curriculum in learning mathematics, but as many as 31% of students did not approve of mathematical classifications of interest & compulsory, besides students objected to the addition of class hours to the 2013 curriculum. The 2013 curriculum also has an impact on how students learn mathematics.